Urban heat island intensity in Chiang Mai city using mobile surveying approach - Pisut Sangnum (2018)
This research aims to evaluate on Urban Heat Island Intensity in Chiang Mai city and to study effects of population density, building density and traffic density on ambient air temperature. The ambient air temperature was measured by thermocouples at a constant altitude of 2 m above the road. The surveyed routes were divided to urban routes and rural routes. The Urban Heat Island Intensity (UHII) was calculated from an average ambient air temperature difference between urban and rural areas. Experimental investigations were carried out in 2 periods, which were a day time (12.30-02.30 pm) and a night time (10.00 pm-00.00 am) on Monday, Wednesday, and Sunday in summer time (March-May, 2013). The results show that the UHII in Chiang Mai city in a day time is +1.1 °C and in a night time is +1.3 °C. Moreover, the population density, building density and traffic density were found to have significant effects on ambient air temperature, especially the population density and building density have direct effect on ambient air temperature. However, the traffic density has direct effect on ambient air temperature only in a day time. © (2014) Trans Tech Publications, Switzerland.